2006
DOI: 10.1002/anie.200600610
|View full text |Cite
|
Sign up to set email alerts
|

Topochemical Polymerization in Supramolecular Polymers of Oligopeptide‐Functionalized Diacetylenes

Abstract: Diacetylene macromonomers functionalized with a β‐sheet‐forming oligopeptide and a hydrogenated poly(isoprene) coil segment self‐assembled into supramolecular polymers with a double‐helical, tubular topology and a diameter of a few nanometers. Subsequent “1D topochemical polymerization” affords poly(diacetylene)s with a conjugated backbone and a high degree of biochemically relevant functionalization, as well as a defined hierarchical structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
126
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(128 citation statements)
references
References 51 publications
0
126
0
2
Order By: Relevance
“…By introducing desired interactions such as H-bonds and charge compensation, highly ordered organizations can be created. [37,38] We synthesized Ac-K 6 -gA, a positively charged derivative of Ac-E 6 -gA, then mixed both materials together. In a series of TEM images, it was shown that instead of vesicles, multilamellar structures were generated from a molar ratio of 0.3 to 0.8.…”
Section: Micelles and Fibersmentioning
confidence: 99%
“…By introducing desired interactions such as H-bonds and charge compensation, highly ordered organizations can be created. [37,38] We synthesized Ac-K 6 -gA, a positively charged derivative of Ac-E 6 -gA, then mixed both materials together. In a series of TEM images, it was shown that instead of vesicles, multilamellar structures were generated from a molar ratio of 0.3 to 0.8.…”
Section: Micelles and Fibersmentioning
confidence: 99%
“…However, occasionally such structures have been found to perform benign biological functions in living organisms, for example as a matrix material that facilitates surface-binding of Escherichia coli bacteria [2], or as a catalytic scaffold for the synthesis of melanin in human melanosomes [3]. Inspired by such potentially useful qualities, more recently, amyloid fibrils have been extensively investigated as functional materials that direct supra-molecular self-assembly [4][5][6], or serve as templates for, e.g. metal nanoparticles [7][8][9] and conjugated (poly)electrolytes [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported a simple method for fabricating n-type 1D nanostructures by the b-sheet assembly of dipeptide-NDI conjugates [8] into either helical nanofibers or twisted nanoribbons. [9] Time-resolved fluorescence anisotropy experiments showed enhanced energy migration within these nanostructures.…”
mentioning
confidence: 99%